EFFECT OF DIFFERENT DOSES OF NEWER INSECTICIDES AGAINST SUCKING PESTS OF OKRA - S. R. PATIL; G. K. LANDE; S. AWASTHI, NIKITA; U. P. BARKHADE (The Bioscan, 2014)
Field experiment was conducted to evaluate and validate the efficacy of some new insecticides against sucking insect pest’s viz., leafhopper, aphid and whitefly in okra. Three sprays of different insecticides viz., Thiamethoxam 25 WG, Lambda cyhalothrin 5 EC and Triazophos 40 EC, at three different concentrations of Thiamethoxam 25 WG, Lambda cyhalothrin 5 EC and Triazophos 40 ECwere made at 15 days interval. This study revealed that, amongst the treatments tested, the cumulative effect of foliar spray of Thiamethoxam 25 WG @ 0.006% was found the most effective against aphids, followed by Lambda cyhalothrin 5 EC @ 0.004%. While, Thiamethoxam 25 WG @ 0.006% was effective against leafhoppers population followed by Thiamethoxam 25 WG @ 0.008%. Also, in case of whitefly the effective treatment recorded was Thiamethoxam 25 WG @ 0.006%. The recommended doses of insecticides were found more effective than other doses.